Politico-cultural-religious milieu of Southeast Asia: an examination of pre-Islamic structures of authority and syncretic practices - Abdul Jalil, Mohd. Noh; Mohd Amin, Wan Mohd Azam; Alias, Majdan (Penerbit Universiti Sains Malaysia, 2019)
This paper analyses the structure of authorities and syncretic practices among the people in Southeast Asia before the spread of Islam in the region. The influence of South Asian tradition and culture in Southeast Asia was evident especially in the social and political spheres. Practices of Southeast Asian empires originated from the South Asian continent. In order to understand those influences this study analyses available materials related to the development of socio-political and cultural-religious environment in Southeast Asia prior to the advancement of Islam in the region. This study concludes that early kingdoms in Southeast Asia adopted the doctrines of devaraja and bodhisattva as the model of governance. This doctrine provides the Rulers with everlasting loyalty from their subjects. At the same time, religious life among the people in Southeast Asia highlights a unique practice. The syncretic practices of the people in Southeast Asia at that time prove that they did not follow blindly religious practices presented to them from the South Asian traditions. They adopt and adapt those practices to suit their own needs at that time.